2010
DOI: 10.1677/joe-10-0282
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects of central leptin infusion and prolactin treatment on pituitary SOCS-3 gene expression in ewes

Abstract: Suppressors of cytokine signalling (SOCS) negatively regulate cytokine-induced signalling pathways and may be involved in leptin and prolactin (PRL) interactions. Herein, we examined the effect of PRL on SOCS-3 mRNA expression in pituitary explants and investigated whether leptin could modify the expression of SOCS-3 mRNA in pituitary explants. In the first experiment, we used pituitaries isolated from 16 ewes decapitated in March, May, July and October (four per month). Tissues were cut into 50 mg explants, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
3
24
0
Order By: Relevance
“…Interesting links also have been found in our previous studies, which indicate that a significant relationship exists between leptin and melatonin (Zieba et al, 2007). We previously demonstrated not only that exogenous leptin is able to modulate melatonin secretion from the ovine pineal gland in vitro (Zieba et al, 2007) and in vivo (Zieba et al, 2008), both in a seasonally dependent manner, but also that melatonin may participate in the regulation of leptin secretion from ovine white adipose tissue explants (Szczesna et al, 2011b). In seasonal mammals, melatonin also regulates photoperiodic changes in plasma concentrations of PRL through a melatonin-dependent oscillator located in the pars tuberalis, which is, as mentioned above, particularly rich in leptin receptors.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Interesting links also have been found in our previous studies, which indicate that a significant relationship exists between leptin and melatonin (Zieba et al, 2007). We previously demonstrated not only that exogenous leptin is able to modulate melatonin secretion from the ovine pineal gland in vitro (Zieba et al, 2007) and in vivo (Zieba et al, 2008), both in a seasonally dependent manner, but also that melatonin may participate in the regulation of leptin secretion from ovine white adipose tissue explants (Szczesna et al, 2011b). In seasonal mammals, melatonin also regulates photoperiodic changes in plasma concentrations of PRL through a melatonin-dependent oscillator located in the pars tuberalis, which is, as mentioned above, particularly rich in leptin receptors.…”
Section: Discussionmentioning
confidence: 55%
“…It is most likely driven by hormonal changes associated with gestation, including mating-induced physiological alternations such as surges in PRL, corpus luteum graviditatis formation and maintenance through enhanced progesterone release and the loss of the cyclical elevations in serum estradiol or the creation of the placenta, which can secrete numerous hormones. Season-and/or dose-dependent effects on leptin synthesis/secretion have been demonstrated with reference to PRL, GH, insulin and melatonin (Szczesna et al, 2011b), sex steroid hormones (Machinal et al, 1999), progesterone (Stelmanska et al, 2012), and placenta-derived factors (Sivan et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the direct receptiveness of AP tissue to PRL in pregnant ewes is lower than that of other tissues; however, to estimate the final sensitivity of target cells, other factors should also be taken into consideration. The results of our previous study indicated that exogenous PRL bidirectionally affects SOCS‐3 expression in ovine pituitary explants in a dose‐ and season‐dependent manner (Szczesna et al, ). As shown in this paper, the expression of SOCS‐3 in the ARC is 6.3‐ to 23.6‐fold higher than that in the AP; this expression difference may counterbalance the responsiveness of both tissues to PRL or allow distinct actions of this hormone.…”
Section: Discussionmentioning
confidence: 88%
“…The results of real‐time PCR are expressed as a function of the cycle threshold (C t ). Expression levels were calculated through relative quantification (RQ) analysis, and the data were analysed using the 2 −ΔΔC t method as described previously (Szczesna, Zieba, Klocek‐Gorka, Misztal, & Stepien, ). In brief, the mean mRNA expression level for each target gene in each sample was normalized to the expression of a reference gene (cyclophilin) and is expressed relative to the expression in the calibrator sample.…”
Section: Methodsmentioning
confidence: 99%
“…Studies conducted by the authors of the present paper indicated that intracerebroventricular leptin infusions were also able to alter hypothalamic SOCS-3 expression in sheep. However, this effect was observed only during long day', but not during short day', conditions (Zieba et al, 2008), while in the pituitary, leptin affects this expression only during short days (Szczesna et al, 2011). This explains the existence of leptin resistance in the hypothalamus with simultaneous maintenance of leptin sensitivity in the pituitary.…”
Section: The Role Of Socs-3 In Seasonal Leptin Resistancementioning
confidence: 89%